Precursors to Probation and Parole Agent Communication Patterns with Female Clients. Issue 2 (14th March 2020) - Smith, Sandi W.; Morash, Merry; Walling, Brandon M.; Adams, Elizabeth A.
ABSTRACT: Supervising agents serve dual roles as they both help and control the over one million women in the United States (U.S.) on probation and parole as the women strive for lives free of substance abuse and crime. Previous research has found that supervising agent communication patterns have a strong influence on these positive outcomes. Little is known, however, about the precursors to the conversational and conformity communication patterns supervising agents use as they serve these dual roles for their female clients. In this study, which is part of a longer-term investigation of communication between women offenders and their supervising agents, multilevel modeling was used to investigate both the characteristics of the agent and of the women they supervise as precursors to agent communication patterns. Supervising agents' client-specific conversational patterns were predicted by their typical self-reported conversational patterns and client assessment of agents' patterns. Conformity patterns of agents were predicted by agent typical self-reported conformity patterns. Also, providing evidence that agents adapt their communication patterns due to recipient characteristics and behaviors, the offender characteristics of adult abuse predicted greater use of a conversation pattern, whereas offender characteristics of child abuse, antisocial attitude, and lower self-efficacy predicted lower use of a conversational pattern. Higher levels of technical violations, recent arrests, and substance abuse predicted greater use of a conformity pattern with specific clients. A conversational pattern promotes a number of positive outcomes, so this suggests the efficacy of shifting agents toward establishing this pattern, especially with women whose personal characteristics were related to the use of a conformity pattern.